The Impact of Family Environment and Students Discipline for the Result of Economics Subject Grade XI SMA Negeri 5 Pematang Siantar Year 2023/2024 - Esra Butarbutar; Herlina Hotmadia Sianipar; Irjen Pardamean Butarbutar (International Journal of Integrated Science and Technology, 2023)
This research aims to gain knowledge regarding the influence of the family environment and learning discipline on the economic learning outcomes of students in class XI at SMA Negeri 5 Pematang Siantar FY 2023/2024 ​This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used is Microsoft Excel . The total population in this study was 102 students. The sample collection technique used was the Slovin formula. The data collection technique used was a questionnaire. Hypothesis data collection techniques use simple regression analysis , multiple regression analysis and coefficient of determination (R2). The results of this research state that: 1) There is a positive and significant influence of the family environment on learning outcomes, this result can be seen in the t test where the calculated t value of learning discipline (0, 0 8) > t table value (1.318) which means the variable is significant. Mukticolinearity Test . The assumption of Tolerance or Variance Inflation Factor (VIF) is capable stated that If VIF > 10 ormark Tolerance < 1.20 so that capablemulticollinearity., or If VIF < 10 or mark Tolerance > 0.10 so it is not capable of multicollinearity. It can be seen in the attachment, (1.20) that Tolerance > 0.10 or Variance Inflation Factor (VIF) < 10, so it can be concluded that the data is not capable of symptoms of multicollinearity.